2000
DOI: 10.1111/j.1472-8206.2000.tb00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blockade unmasks a depressor response to endothelin antagonists in rats

Abstract: Endothelin (ET) antagonists do not decrease blood pressure in normal rats. Since angiotensin II (AII) and ET both induce smooth muscle cell contraction through the same transduction pathways we designed experiments to assess whether blockade of the renin angiotensin system would unmask a vasodilatory response to ET receptor antagonists in rats. For this purpose, we tested the effect on arterial blood pressure of the mixed ETA-ETB receptor antagonist bosentan or of the ETA antagonist BQ-123 in the absence or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Therefore, our data suggest that an increased vasoconstrictor effect of ET limits the systemic vasodilation induced by AT 1 blockade. These observations are corroborated by findings in dogs of either sex (8) and male rats (31), in which combined blockade of ET A /ET B and AT 1 receptors resulted in decreases in SVR and aortic blood pressure that were larger than the sum of the decreases produced by individual blockade of either ET A /ET B or AT 1 receptors alone. Interestingly, the decreases in blood pressure induced by combined blockade ET A /ET B or AT 1 receptors in these studies are larger than those observed in the present study, which may have been due to the presence of pentobarbital anesthesia.…”
Section: Integrated Regulation Of Resistance Vessel Tone By Et and Ansupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, our data suggest that an increased vasoconstrictor effect of ET limits the systemic vasodilation induced by AT 1 blockade. These observations are corroborated by findings in dogs of either sex (8) and male rats (31), in which combined blockade of ET A /ET B and AT 1 receptors resulted in decreases in SVR and aortic blood pressure that were larger than the sum of the decreases produced by individual blockade of either ET A /ET B or AT 1 receptors alone. Interestingly, the decreases in blood pressure induced by combined blockade ET A /ET B or AT 1 receptors in these studies are larger than those observed in the present study, which may have been due to the presence of pentobarbital anesthesia.…”
Section: Integrated Regulation Of Resistance Vessel Tone By Et and Ansupporting
confidence: 76%
“…In contrast to the ET-stimulating effects of exogenous ANG II, endogenous ANG II appears to suppress the ET system. Thus, in anesthetized rats (31) and dogs (8), combined blockade of ET A /ET B and AT 1 receptors resulted in a decrease in SVR that was larger than the sum of the decreases in SVR produced by individual ET A /ET B and AT 1 blockade. These observations could be interpreted to suggest that the lack of effect of AT 1 blockade on PVR previously reported in swine (3) and dogs (8) may have been due to a concomitant increased ET vasoconstrictor influence.…”
mentioning
confidence: 99%
“…It is well known that the regulation of arterial tone is complex and involves numerous neuronal, endocrine, and autacoid interactions. It has recently been demonstrated that blockade of the renin-angiotensin system unmasks a potent vasodilatory response to ET antagonists in normotensive anesthetized rats (29). The authors conclude that this suggests that endogenous ET-1 indeed contributes to the normal vasodepressor tone and that this contribution may be evidenced after blockade of the reninangiotensin system.…”
Section: Table 3 Effect Of Et Antagonists On the Et-1-induced Attenumentioning
confidence: 72%
“…8,16 Even when selective ET A blockade has been performed by infusing drugs locally in the forearm of normal subjects, conflicting results have been obtained, ranging from no changes 17 to a 40% increase in baseline blood flow. 18 On the other hand, studies in both normal dogs and rats undergoing simultaneous systemic blockade of renin-angiotensin system (RAS) with either ACE inhibitors (ACEI) 4,5 or AT 1 receptor antagonists (AIIRA) 19 have shown that hypotension and, primarily, marked renal vasodilation resulted from ET A or mixed ET A /ET B blockade. For instance, Berthold et al 4,5 have reported that, in dogs receiving both ACEI trandolapril and ET A blocker LU135252, renal blood flow (RBF) increased to an extent 3 to 4 times larger than that observed with ET A blockade alone.…”
mentioning
confidence: 99%